2019
DOI: 10.1116/1.5079834
|View full text |Cite
|
Sign up to set email alerts
|

Improved performance and stability of In-Sn-Zn-O thin film transistor by introducing a meso-crystalline ZrO2 high-k gate insulator

Abstract: Electrical characteristics and reliability of an In-Sn-Zn-O (ITZO) thin film transistor (TFT) using ZrO2 as a high-k gate insulator were investigated. Varying the atomic layer deposition process temperature caused differences in the ZrO2 thin film chemical state and microstructure. Corresponding changes in the electrical properties of the thin film were evaluated. While the ZrO2 thin film deposited at 300 °C exhibited an excellent thin film property, the best TFT performance as measured by subthreshold swing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…These represent the contributions of metal—oxygen bonds without oxygen vacancies, in oxygen‐deficient regions, and in hydroxide bonds, respectively. [ 22 ] The OH peaks’ contribution to the O1s spectrum is 6.2%, 6.9%, and 10.8% at plasma powers 50, 100, and 1000 W, respectively. OH bonding is observed in both the Zr3d and O1s spectra, and the ratio of OH‐related peaks increases as plasma power increases.…”
Section: Resultsmentioning
confidence: 99%
“…These represent the contributions of metal—oxygen bonds without oxygen vacancies, in oxygen‐deficient regions, and in hydroxide bonds, respectively. [ 22 ] The OH peaks’ contribution to the O1s spectrum is 6.2%, 6.9%, and 10.8% at plasma powers 50, 100, and 1000 W, respectively. OH bonding is observed in both the Zr3d and O1s spectra, and the ratio of OH‐related peaks increases as plasma power increases.…”
Section: Resultsmentioning
confidence: 99%
“…However, when Al 2 O 3 was used as a dopant, it inhibited coalescence of the dielectric, resulting in a smaller grain crystal structure of the matrix dielectric. In this regard, a "mesocrystalline" structure was suggested for reducing leakage current [25,46]. The mesocrystalline structure consisted of partially crystallized grains incorporated in an amorphous matrix.…”
Section: Bulk-related Leakage Current Conductionmentioning
confidence: 99%
“…Numerous studies have reported that ITZO-TFTs possess high μ FE values. In 2021, Shiah et al found an ITZO-TFT with an extremely high μ FE of 70 cm 2 V –1 s –1 , demonstrating the potential of these TFTs. However, the origin of their high μ FE has yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%